TANGGUNG JAWAB ORANG TUA DALAM PENDIDIKAN ANAK BERPOLA PEDAGOGIK TRANSFORMATIF KRISTIANI - Sensius Amon Karlau (BONAFIDE: Jurnal Teologi dan Pendidikan Kristen, 2022)
Today there are still Christian parents who do not understand their responsibilities as educators in inculcating Christian faith values ​​for children from an early age at home. This study aims to explore the concept of Christian education for children as part of the responsibility of parents related to the vocation of Christian transformative pedagogy. The method used is descriptive qualitative with a literature study approach. The results showed that Christian transformative pedagogy in Christian education for children focuses on the individuation process by Christian parents in educating autonomous children. This process is communicative and dialogical by a child, for himself and his parents as "I and the other-I" and God as the Other-I. The same process is carried out by parents to their children in their proximal environment as a process of individuation between "I and the other-me" in a future-oriented Christian transformative pedagogic call through creative imagination so that children become adults in Christ according to Bible.